A comparative study on structural design alternatives for twisted tall buildings with outriggers. (2nd November 2022) - Demirel, G. N.; Ay, B. Ö.
Abstract : Tall buildings are seen as iconic landmarks because of their bold effect on the city silhouette. To control this bold effect in an aesthetically desired manner, designers search for intriguing forms such as twisted buildings. There are two main approaches for designing the structural system of a twisted tall building. In the first approach, the twisted form of the building is obtained only by the rotation of the floors, and the structural system is maintained in a conventional, perpendicular way. Alternatively, the structural system and the floors of the building twist together. This study designates these as non-adaptive and adaptive, respectively. With different heights and angles of twist, non-adaptive and adaptive tall building models are created and analysed under the combined effect of wind and gravity loads. The dynamic properties, drift, moment, and torsion demands are compared to scrutinize and assess the potentials and limitations of these alternative approaches.